LEARNER-CENTERED PEDAGOGIES: TRANSFORMING EDUCATION FOR THE 21ST CENTURY - Aadil Hussain Mir (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
Learner-centered pedagogy (LCP) is an innovative and transformative approach that shifts the traditional education model from teacher-driven instruction to a student-focused learning environment. This pedagogy emphasizes active engagement, collaboration, and personalized learning, encouraging students to take ownership of their education. Rooted in constructivist, experiential, and humanistic learning theories, LCP fosters critical thinking, problem-solving, and lifelong learning skills essential for the 21st century. Despite its numerous benefits, such as improved academic performance, increased motivation, and deeper knowledge retention, LCP faces significant challenges, including teacher resistance, assessment difficulties, and resource constraints. This paper explores the principles, strategies, benefits, and challenges of LCP, supported by theoretical frameworks and empirical evidence. Additionally, it examines successful case studies from different educational settings and discusses the future of learner-centered approaches, including the integration of technology, AI-driven personalized learning, and policy reforms. By embracing LCP, educators and policymakers can create more inclusive, adaptive, and effective educational systems that prepare students for the complexities of modern society.